2010
DOI: 10.1007/s00381-010-1330-8
|View full text |Cite
|
Sign up to set email alerts
|

Craniopharyngiomas in children: how radical should the surgeon be?

Abstract: Radical removal of SEVCs is safer than of IEVCs despite an apparent involvement of hypothalamus. In majority of cases, they may be distinguished by indirect MRI signs; in others only according to operation findings; final decision about the optimal extent of tumor removal should be made during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 37 publications
0
30
1
1
Order By: Relevance
“…According to Steno et al, primary supradiaphragmatic craniopharyngiomas differ from originally subdiaphragmatic, and are associated with a less favorable prognosis [25,34]. However, the suprasellar extension of a subdiaphragmatic craniopharyngioma might be still subdiaphragmatic; in this case, the diaphragm covers most of the suprasellar portion, making the tumor less adherent to neurovascular structures.…”
Section: Correlations Between Neuroimaging Characteristics and Postopmentioning
confidence: 94%
See 2 more Smart Citations
“…According to Steno et al, primary supradiaphragmatic craniopharyngiomas differ from originally subdiaphragmatic, and are associated with a less favorable prognosis [25,34]. However, the suprasellar extension of a subdiaphragmatic craniopharyngioma might be still subdiaphragmatic; in this case, the diaphragm covers most of the suprasellar portion, making the tumor less adherent to neurovascular structures.…”
Section: Correlations Between Neuroimaging Characteristics and Postopmentioning
confidence: 94%
“…Steno et al [34] and Pascual et al [35] reported a higher hypothalamic complication rate, in case of tumors with intraventricular extension as compared with purely extraventricular tumors [34]. To preserve the hypothalamic function, it is very important to distinguish between suprasellar extraventricular and suprasellar intra-and extra-ventricular craniopharyngioma.…”
Section: Correlations Between Neuroimaging Characteristics and Postopmentioning
confidence: 98%
See 1 more Smart Citation
“…Causes of late mortality include those directly related to the tumor or its treatment such as progressive disease with multiple recurrences, chronic hypothalamic insufficiency, hormonal deficiencies, cerebrovascular disease, and seizures (26,38,40,48). Other disease-related causes of mortality have been described, including decreased mineral bone density and non-alcoholic steatohepatitis, leading to liver cirrhosis in some cases (38,40).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Progressive hypothalamic involvement correlated with larger postoperative weight gains. Steno et al [13] reported a higher hypothalamic complication rate, in case of tumors with intraventricular extension as compared with purely extraventricular tumors. To preserve the hypothalamic function, the authors recommend to distinguish between suprasellar extraventricular and suprasellar intra-and extraventricular craniopharyngioma.…”
Section: Grading Systems For Hypothalamic Involvement/ Lesions In Cpmentioning
confidence: 99%